The Role of an IL-10/Hyaluronan Axis in Dermal Wound Healing - Singampalli, Kavya L.; Balaji, Swathi; Wang, Xinyi; Parikh, Umang M.; Kaul, Aditya; Gilley, Jamie; Birla, Ravi K.; Bollyky, Paul L.; Keswani, Sundeep G. (Frontiers in Cell and Developmental Biology, 2020)
Scar formation is the typical endpoint of postnatal dermal wound healing, which affects more than 100 million individuals annually. Not only do scars cause a functional burden by reducing the biomechanical strength of skin at the site of injury, but they also significantly increase healthcare costs and impose psychosocial challenges. Though the mechanisms that dictate how dermal wounds heal are still not completely understood, they are regulated by extracellular matrix remodeling, neovascularization, and inflammatory responses. The cytokine IL-10 has emerged as a key mediator of the pro- to anti-inflammatory transition that counters collagen deposition in scarring. In parallel, the high molecular weight glycosaminoglycan hyaluronan is present in the extracellular matrix and acts in concert with IL-10 to block pro-inflammatory signals and attenuate fibrotic responses. Notably, high concentrations of both IL-10 and high molecular weight hyaluronan are produced in early gestational fetal skin, which heals scarlessly. Since fibroblasts are responsible for collagen deposition, it is critical to determine how the concerted actions of IL-10 and hyaluronan drive their function to potentially control fibrogenesis. Beyond their independent actions, an auto-regulatory IL-10/hyaluronan axis may exist to modulate the magnitude of CD4+ effector T lymphocyte activation and enhance T regulatory cell function in order to reduce scarring. This review underscores the pathophysiological impact of the IL-10/ hyaluronan axis as a multifaceted molecular mechanism to direct primary cell responders and regulators towards either regenerative dermal tissue repair or scarring.